Exploring 3D Navigation: Combining Speed-coupled Flying with Orbiting - Tan, Desney; Robertson, George; Czerwinski, Mary (CHI 2001, Human Factors in Computing Systems, 2001)
We present a task-based taxonomy of navigation techniques for 3D virtual environments, used to categorize existing techniques, drive exploration of the design space, and inspire new techniques. We briefly discuss several new techniques, and describe in detail one new technique, Speed-coupled Flying with Orbiting. This technique couples control of movement speed to camera height and tilt, allowing users to seamlessly transition between local environment-views and global overviews. Users can also orbit specific objects for inspection. Results from two competitive user studies suggest users performed better with Speed-coupled Flying with Orbiting over alternatives, with performance also enhanced by a large display.